A comparative study in time management between track and field sports players and volleyball players - Matrood, Maysaa (Journal of Physical Education, 2024)
The aim of the research was to study the ability of track and field players and volleyball players to manage time and to compare time management skills between volleyball players and track and field players. The descriptive approach was used, and the sample included 10 track and field players and 15 volleyball players. Merrill Douglas’s time management questionnaire was approved after verifying its validity and reliability. The data was statistically analyzed using the arithmetic mean, standard deviation, hypothetical mean, and t-test. The results showed the weak ability of track and field players and volleyball players to manage time. The researcher recommended organizing educational courses to improve the players’ time management skills, enhancing material and moral incentives, while adhering to the training dates specified by the coaches, and conducting studies on time management among coaches and referees.